Studying prostate cancer cell lines metabolome with FTIR spectroscopy - Santos, Francisco José Furtado (2020)
Cancer is one of the leading causes of death worldwide, with prostate cancer being the second most common neoplasia amongst men. Thus, strategies that can provide an early diagnosis of this disease are of great importance. Because biochemical alterations precede morphological changes in cells, cancer metabolome has gained relevance and may contribute to the understanding of tumor biology and to the identification of early diagnostic biomarkers. Fourier-transform infrared (FTIR) spectroscopy is a metabolomics technique that, unlike staining procedures and other histopathologic approaches, is rapid, non-destructive and does not require reagents. This technique probes the biochemical composition of the analyzed samples and allows the discrimination of samples with distinct metabolic profiles, thus discriminating cancerous and non-cancerous samples. The main goals of this work were to explore the ability of FTIR spectroscopy, coupled with multivariate analysis, in the: (1) discrimination between prostate cancer cells derived from a primary tumor (22Rv1) and normal epithelial cells (PNT1A and PNT2); and (2) discrimination between prostate primary tumor cells (22Rv1) from metastatic cells derived from two distinct sites (LNCaP, from lymph node, and PC-3, from bone). A clear discrimination between the different prostate cell lines was observed, indicating that they exhibit different metabolic profiles. This discrimination can be attributed to an altered lipid metabolism (3000-2800 cm-1, 1800-1700 cm-1 and 1500-1400 cm-1) and the presence of protein aggregates (1622 cm-1). Our results suggest that studying cancer metabolome with FTIR spectroscopy not only allows the understanding of tumor pathogenesis, but also may be a valuable tool for the identification of early diagnostic biomarkers, which are crucial for a good prognosis.